(untitled) (Perner’s Contacts, 2017)
The paper deals with the price mix used by the low cost air carriers with special focus on pricing specifics in case of a la carte pricing. The first part describes price mix specifics by low cost air carriers and the importance of a la carte pricing within this mix. General way-outs are considered when realizing of the analysis focused on specifying of the application degree and form when using a la carte pricing. Gained findings are discussed and evaluated in the conclusion of the paper.